AMINO ACID LEVELS AND PATTERNS IN WILD TURKEY POULTS AND THEIR FOOD ITEMS IN MISSISSIPPI - George A. Hurst; William E. Poe (Wildlife Society Bulletin)
Abstract: Amino acid analyses of whole‐body, excluding feathers, carcasses of captive eastern wild turkey poults (Meleagris gallopavo silvestris) age 1 to 4 weeks, revealed no major differences in levels of 11 essential amino acids. The most abundant essential amino acids, in descending order, occurred in 3 groups. The first group included leucine, lysine and arginine; the second group valine, threonine, phenylalanine, isoleucine and tyrosine; and the third group was composed of histidine, methionine and tryptophan. Amino acid analyses of insects from 7 orders (Coleoptera, Homoptera, Hemiptera, Lepidoptera, Orthoptera, Hymenoptera and Diptera), and spiders (Arachnida) showed that protein was 76% in spiders and 57% in insects. Amino acid levels and patterns of the Arthropods were similar, and were very similar to the levels and patterns (fingerprints) in wild turkey poult carcasses. Sedge (Carex spp.) and panic grass (Panicum spp.) seeds contained 11.1 and 13.6% protein, while dewberry (Rubus sp.) fruits contained only 6.1% protein. Amino acid levels and patterns varied among the plant items, but there were similarities to turkey poult amino acid patterns. Calculations based on minimum amino acid requirements indicated that a 7‐day‐old poult weighing 70 g, live weight, would have to eat about 12 g, live weight, of insects or 9 g of spiders to meet the minimum amino acid requirements for that 1 day.